Feasting and polis institutions - Eijnde, Floris van den, 1975-; Blok, Josine Henriëtte, 1953-; Strootman, Rolf, 1968- (Mnemosyne. Supplements,, 2018)
Feasting and commensality were vital to the great resilience of the polis, Greece's most characteristic and enduring form of political organization. Exploring a wide array of commensal practices, Feasting and Polis Institutions reveals how feasts defined the religious and political institutions of the Greek citizen-state. Taking the reader from the Early Iron Age to the Imperial Period, this volume launches an essential inquiry into Greek power relations. Focusing on the myriad of patronage roles at the feast and making use of a wide variety of methodologies and primary sources, including archaeology, epigraphy and literature, Feasting and Polis Institutions argues that in ancient Greece political interaction could never be complete until it was consumed in a very literal sense.